2014
DOI: 10.1242/jeb.107235
|View full text |Cite
|
Sign up to set email alerts
|

Migratory blackcaps tested in Emlen funnels can orient at 85 but not at 88 degrees magnetic inclination

Abstract: Migratory birds are known to use the Earth's magnetic field as an orientation cue on their tremendous journeys between their breeding and overwintering grounds. The magnetic compass of migratory birds relies on the magnetic field's inclination, i.e. the angle between the magnetic field lines and the Earth's surface. As a consequence, vertical or horizontal field lines corresponding to 0 or 90 deg inclination should offer no utilizable information on where to find North or South. So far, very little is known ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
44
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(47 citation statements)
references
References 43 publications
2
44
0
Order By: Relevance
“…More specifically, we have presented a version of the radical pair model that could potentially explain the magnetic compass precision observed for night-migratory songbirds (32,33). The feature that makes this feasible, referred to as a spike, emerges naturally for cryptochrome-based radical pairs when the lifetime of the spin coherence exceeds 1 μs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…More specifically, we have presented a version of the radical pair model that could potentially explain the magnetic compass precision observed for night-migratory songbirds (32,33). The feature that makes this feasible, referred to as a spike, emerges naturally for cryptochrome-based radical pairs when the lifetime of the spin coherence exceeds 1 μs.…”
Section: Discussionmentioning
confidence: 99%
“…Because the magnetic compass seems to be the dominant source of directional information (31), and the only compass available at night under an overcast (but not completely dark) sky, migratory birds must be able to determine their flight direction with high precision using their magnetic compass. Studies have shown that migratory songbirds can detect the axis of the magnetic field lines with an accuracy better than 5° (32,33). Any plausible magnetoreception hypothesis must be able to explain how such a directional precision can be achieved.…”
mentioning
confidence: 99%
“…However, experiments at locations with equally large magnetic inclinations, like Rybachy (70° inclination), do not report the same problems that we find at Stensoffa (Kavokin et al ). Also, orientation experiments performed at even higher latitudes than southern Sweden have shown that migrating birds are able to detect magnetic compass information at very steep angles of inclination (as steep as 98°; Sandberg et al , , Åkesson et al , , , Gudmundsson and Sandberg , Muheim and Åkesson , Muheim et al , Lefeldt et al ). Weindler et al () pointed out that the problem of steep inclination might be more pronounced in hand‐raised birds than in wild‐caught birds that had access to a variety of other cues (stars, sun, etc.)…”
Section: Effects Of Capture and Experimental Sitesmentioning
confidence: 99%
“…Sandberg et al 1998; Åkesson et al 1995, 2001a). In the laboratory, songbirds have been shown to detect magnetic fields as steep as 85° inclination angle (Lefeldt et al 2015), while under natural conditions, the behavioural responses suggest an ability to detect even steeper magnetic fields (Sandberg et al 1998; Åkesson et al 2001a, b, 2005). Polar regions are further exposed to particularly large temporal variations of geomagnetic field parameters caused by geomagnetic storms (Skiles 1985), which may be challenging for compass orientation and navigation.…”
Section: Introductionmentioning
confidence: 99%